Palatability of two artificial feeds for reindeer - Rognmo, Arne; Bye, Karstein (Rangifer, 1990)
Two groups of 15 reindeer were used to test the palatability of two artificial diets. None of the animals had experienced the diets before. Trials were carried out from April to mid May. Each group of animals was kept in a separate corral (600 sq. meters). Both groups were fed lichens for three days befort trials began. Then they were offered a concentrate feed (RF-80) or «Mill Waste Product» (MWP) ad libitum. Both groups ate little or nothing for the first three days of the trial and so lichens were mixed with the two experimental feeds. The mean voluntary food intake of the RF-80-group increased from 0.8 Kg/day/animal to 1.8 Kg/day/animal after three weeks. A mixed feed, RF-80/lichen, was only used the first day for animals in the RF-80 group. Reindeer refused to eat MWP for twelve days despite mixing it with lichens. They were then offered RF-80 ad lib. without a mixture of lichens. The mean voluntary intake of these animals increased from 1.3 Kg RF-80/day/animal on day 13 to 2.3 Kg/day/animal by day 26. Two calves in the MWP-group got diarrhoea after refeeding with RF-80.